2013
DOI: 10.1097/ncc.0b013e318288d3ce
|View full text |Cite
|
Sign up to set email alerts
|

The Art of Age-Appropriate Care

Abstract: Young people must be kept at the center of interactions in recognition of their stated needs of engagement, of individually tailored information and support unproxied by parents/family. Age-appropriate information and support services that help young people deal with the impact of cancer on daily life and life after cancer must be made available. If we are to develop services that meet need, patient experience surveys must be influenced by patient involvement. Young people can be successfully involved in plann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 40 publications
1
57
0
Order By: Relevance
“…All studies were observational; none employed experimental or quasi-experimental designs. Eleven studies used qualitative or survey methods to obtain input from patients, 4,7,[18][19][20][21][22][23][24][25][26] and 17 studies were narrative reports describing one group's experiences with engagement. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] The remaining seven studies were descriptions of specific initiatives reported on websites [44][45][46][47][48][49][50] ( Table 1 and Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All studies were observational; none employed experimental or quasi-experimental designs. Eleven studies used qualitative or survey methods to obtain input from patients, 4,7,[18][19][20][21][22][23][24][25][26] and 17 studies were narrative reports describing one group's experiences with engagement. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] The remaining seven studies were descriptions of specific initiatives reported on websites [44][45][46][47][48][49][50] ( Table 1 and Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…cians. 20,38,39,47,49 Seven studies were classified as sufficiently descriptive 7,18,19,[23][24][25][26] The purposes of engagement included identifying patient-centered research topics or agendas, 19,23,29,36,39 identifying outcomes important to patients or developing measures relevant to patients' needs, 7,19,20,23,25,26 increasing recruitment or enrollment through development of patient-centered study designs, 4,18,21,24,27,30,31,41 and incorporating the patient perspective into study design 19,25,35,39,40 (Table 2, Table 3). Patients and other stakeholders were most commonly engaged in the preparatory stage (n= 19 for agenda setting) 4, 7, 19, 20, 23, 25, 28, 29, 32, 35, 36, 39- (Table 4 [online]).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations